WHEN THINKING FAILS: MISCONCEPTIONS AND THE ROLE OF COGNITIVE DISSONANCE IN MATHEMATICS TEACHER EDUCATION - Surya Sari Faradiba; Alifiani Alifiani; Fadhila Kartika Sari; Isbadar Nursit; Ruhaisa Deramea (Program Studi PGSD Universitas Flores, 2026)
Misconceptions in mathematics persist as a problem in teacher education, often rooted in unresolved cognitive conflicts. This study aims to explore how cognitive dissonance contributes to the formation and persistence of mathematical misconceptions in a prospective mathematics teacher. Conducted at a private university in Malang, Indonesia, this research employs a qualitative case study design with one participant, purposefully selected based on prior conceptual errors. Data were collected through task-based assessments and semi-structured interviews, and were then analyzed thematically. The findings show that the participant exhibited stable misconceptions in key mathematical areas, particularly when encountering information that challenged prior beliefs. Rather than adjusting or restructuring incorrect knowledge, the participant displayed psychological resistance through justification, minimization, and selective attention to confirming evidence. These mechanisms serve to reduce internal discomfort (dissonance) without engaging in conceptual change. As a result, the erroneous mental model is maintained despite exposure to correct information. This highlights the critical role of cognitive dissonance in reinforcing misconceptions through defensive cognitive strategies.